(untitled) (Scientific journal of the Fergana State University, 2023)
The basis of the theory of translation it is necessary to establish certain patterns by comparing the features of the vocabulary and grammatical structure, the stylistic use of the language means of English, French, German and Russian, on the one hand, and the analysis of translation practice, on the other hand. So, the main position of this theory is the functional principle of such correspondences. They are very essential to use during the lesson.